Stranger in a Strange Land: Old Chair, New University - Juliet V Spencer; Vagner M Whitehead; George A King (Academic Chairpersons Conference Proceedings, 2020)
There are opportunities and challenges associated with appointing a chair from within and from outside the organization. This discussion will consider multiple aspects and focus on considerations for changing institutions to assume the chair position.
Keywords: Educational Leadership; Communications; Adaptation; Transition; Cultural Inclusion